Eine einfältige Erzählung: Zu Falters und Hasses Text über "Die Geographie und das Mensch-Natur-Verhältnis" - Hard, Gerhard (ERDKUNDE, 2002)
This article is a rejoinder to Falter's and Hasse's article (in this issue). Among other themes I will touch their uncritical reception of authors outside geography and their emphasis on ideas with affinity to fascist ideologies (according to Heinrich 1991). The article concludes with reflections on interpretation method in geography.